The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.5325/critphilrace.11.1.0033
|View full text |Cite
|
Sign up to set email alerts
|

Ground Down and Locked in a Paperweight: Toward a Critical Psychology of Caste-Based Humiliation

Abstract: Psychology limits the scope of raising questions important in the caste context. While psychology focuses on why and how people feel humiliated, the question in the caste context is why and how people do not feel humiliated despite incessant and gratuitous attacks on their dignity and self-worth. This article argues that psychology needs to adopt a critical orientation to address the experience of caste-based humiliation. The anticaste perspective of B. R. Ambedkar provides a critical orientation and psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…It is equally important to examine how the oppressed caste groups deal with the everyday challenges thrown at them owing to their identity position. For example, Jogdand (2023) suggested that one form of resistance could be the mere appraisal of humiliation. Along the same lines, the mere existence of Dalits in a digital context dominated by opposing and suppressing voices maybe perceived as an act of resistance.…”
Section: Navigating Conformity Biasmentioning
confidence: 99%
“…It is equally important to examine how the oppressed caste groups deal with the everyday challenges thrown at them owing to their identity position. For example, Jogdand (2023) suggested that one form of resistance could be the mere appraisal of humiliation. Along the same lines, the mere existence of Dalits in a digital context dominated by opposing and suppressing voices maybe perceived as an act of resistance.…”
Section: Navigating Conformity Biasmentioning
confidence: 99%
“…Overall, psychology has worked as a technique for legitimizing racism and ignoring power inequalities and structural determinants of human oppression. In India, psychology has perpetuated the caste order and denigrated the Dalits and lower castes (Jogdand 2023). In this sense, psychology should be construed as a form of power that is used to control, influence, and coerce Dalit and Black/African people.…”
Section: Psychology As a Form Of Powermentioning
confidence: 99%
“…Graded inequality creates an affective climate in which various castes harbor feelings that form "[an] ascending scale of hatred and descending scale of contempt" (Ambedkar 1987: 48). In addition, Ambedkar approached emotions as group-based performative entities critical to building solidarities and mobilizing collective action (Jogdand 2023). Ambedkar's mobilization discourse is replete with his innovative usage of cognitive and affective categories.…”
Section: 'Psychology Of Caste' and Ambedkar's Psychological Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only through the casteist slurs but as Das (2021) writes, the expressions "You dress so well, you don't look like Dalit"… "I could never imagine you are Dalit", etc., are also casteist and discriminatory in nature. Jogdand (2023) shows how these comments constrain Dalits to an upper-caste 1 gaze, leading to their humiliation. It is important to ask oneself what stereotypical expectation or casteist associations one reproduces through this language.…”
Section: Introductionmentioning
confidence: 99%